Efficacy and safety of strontium ranelate in the treatment of knee osteoarthritis: results of a double-blind, randomised placebo-controlled trial. Issue 2 (1st November 2012) - Reginster, Jean-Yves; Badurski, Janusz; Bellamy, Nicholas; Bensen, William; Chapurlat, Roland; Chevalier, Xavier; Christiansen, Claus; Genant, Harry; Navarro, Federico; Nasonov, Evgeny; Sambrook, Philip N; Spector, Timothy D; et al.
Abstract : Background: Strontium ranelate is currently used for osteoporosis. The international, double-blind, randomised, placebo-controlled Strontium ranelate Efficacy in Knee OsteoarthrItis triAl evaluated its effect on radiological progression of knee osteoarthritis. Methods: Patients with knee osteoarthritis (Kellgren and Lawrence grade 2 or 3, and joint space width (JSW) 2.5–5 mm) were randomly allocated to strontium ranelate 1 g/day (n=558), 2 g/day (n=566) or placebo (n=559). The primary endpoint was radiographical change in JSW (medial tibiofemoral compartment) over 3 years versus placebo. Secondary endpoints included radiological progression, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, and knee pain. The trial is registered (ISRCTN41323372 ). Results: The intention-to-treat population included 1371 patients. Treatment with strontium ranelate was associated with smaller degradations in JSW than placebo (1 g/day: −0.23 (SD 0.56) mm; 2 g/day: −0.27 (SD 0.63) mm; placebo: −0.37 (SD 0.59) mm); treatment-placebo differences were 0.14 (SE 0.04), 95% CI 0.05 to 0.23, p<0.001 for 1 g/day and 0.10 (SE 0.04), 95% CI 0.02 to 0.19, p=0.018 for 2 g/day. Fewer radiological progressors were observed with strontium ranelate (p<0.001 and p=0.012 for 1 and 2 g/day). There were greater reductions in total WOMAC score (p=0.045), pain subscore (p=0.028), physical function subscore (p=0.099) and knee pain (p=0.065) with strontium ranelate 2 g/day. Strontium ranelate was well tolerated. Conclusions: Treatment with strontium ranelate 1 and 2 g/day is associated with a significant effect on structure in patients with knee osteoarthritis, and a beneficial effect on symptoms for strontium ranelate 2 g/day.